2019
DOI: 10.1038/s41598-019-56046-1
|View full text |Cite
|
Sign up to set email alerts
|

Land use affects lowland stream ecosystems through dissolved oxygen regimes

Abstract: The aim of the present study was to assess the impact of surrounding land use on the structure and functioning of lowland stream ecosystems. To this end, five different land use types were selected (forest, extensive grassland, intensive grassland, cropland and wastewater treatment plant) each represented by four replicate streams, in which diel dissolved oxygen concentrations were recorded, sediment and water quality parameters were measured and macroinvertebrate community composition was determined. Chironom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 56 publications
1
9
0
2
Order By: Relevance
“…In general, the metabolic P and R rates found in our study sites lie between the rates found in other stream systems, with lower P rates at forested study sites and higher at more anthropogenically influenced streams with higher proportions of agricultural and urban land use 76 79 .…”
Section: Discussionsupporting
confidence: 70%
“…In general, the metabolic P and R rates found in our study sites lie between the rates found in other stream systems, with lower P rates at forested study sites and higher at more anthropogenically influenced streams with higher proportions of agricultural and urban land use 76 79 .…”
Section: Discussionsupporting
confidence: 70%
“…High oxygen demand often occurs in reaches with high levels of organic matter inputs and nutrient concentrations. This can occur in agricultural settings (dos Reis Oliveira et al 2019 ) or downstream from wastewater treatment plants (Ortiz and Puig 2007 ). Low DO can also occur in urban streams, where low aeration rates from altered geomorphology occur (e.g., stagnant pools; Blaszczak et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wide impoundments may therefore accumulate and retain organic matter and fine mineral sediments, which may interact with land surface runoff from cultivated areas[ 19 ]. Runoff and accumulation of excess nutrients—including nitrogen (N), phosphorus (P), and carbon (C) common in agricultural fertilizers and livestock manure—may further increase biological oxygen demand [ 54 , 55 ], even at the relatively low levels of cultivated land in our study areas (0–2.6%). Although this study focuses on human-made dams, previous research has suggested that dams created by beaver ( Castor canadensis and Castor fiber ) may slightly decrease impoundment and downstream DO as compared to upstream [ 56 ].…”
Section: Discussionmentioning
confidence: 99%